Upaya Pengurangan Risiko Kecelakaan Kerja Menggunakan Metode Hazard Identification, Risk Assessment, Risk Control (HIRARC) di PT. X - Sylvester Mario; Kriswanto Widiawan (Jurnal Titra, 2022)
PT. X is a kitchen equipment manufacturing company that has been operating since 1997. During its operation, PT. X already has an OHS policy, but the execution of the policy is still not detailed. Therefore, the purpose of this final project is to use HIRARC method to identify hazards, assess risks, and provide suggestions for control in the production process . By using HIRARC method, risks of existing work accidents can be analyzed and can be reduced. The initial stages of this final project are direct observations and interviews with the head of production. Then, identification of hazards, risk assessment, and finally the provision of control proposals so that the potential for work accidents can be minimized. After the analysis, it was found that there are 5 hazards with a high risk rating value, 14 hazards with a Significant risk rating value, 7 hazards with a Medium risk rating value, and 1 hazard with a Low risk rating value. A risk control design is carried out, if the proposal is carried out, the potential for reducing the level of hazard risk is 1 hazard with a Medium risk rating value and 26 hazards with a Low risk rating value.